Drink Full and Descend: The Horror of Twin Peaks: The Return - Lindsay Hallam (New York City College of Technology, 2020)
Throughout the work of director and co-creator David Lynch images of horror recur, as the mundane and the ordinary becomes ominous and terrifying. The home and the self–central to feelings of safety and security–are destabilized in Lynch’s works, revealed as inherently unstable and subject to constant change. The fragmented self destabilizes everything around it, reverberating throughout the home and even further still, destabilizing deep-rooted ideas about America’s sense of itself as a place of steadfast reason and righteous justice. This paper explores the use of horror in Twin Peaks: The Return, from its employment of common genre tropes to its engagement with deeper philosophical ideas about horror as something that goes deeper than just thrills and scares.